Exposure to Bone Injuries in the Farming and Herding Populations in Medieval and Early Modern Croatia (Archaeologia Adriatica, 2022)
Since the dawn of humanity, people have been engaged in some sort of agriculture. Due to a number of challenges and perils that it brings, presently it is classified among three most hazardous occupations. On the one hand, farming implies use of various agricultural implements, climbing ladders, silos etc., while transhumant herding refers to everyday contact with big animals and moving in karsty landscape. The main aim of this research was to determine if there is a difference in the pattern and frequencies of antemortem traumas on long bones between dominantly farming populations and dominantly herding populations. The frequencies of traumas on male and female population in the samples were also investigated. All perimortem traumas in the samples were caused by intentional interpersonal violence and therefore were left out of this research. Three composite samples were compared. The first sample comprises 230 skeletons from the sites dated to the Early and High Middle Ages (9th - 13th century), the second sample includes 401 skeletons recovered from the sites dating to the High and Late Middle Ages (13th - 16th century), and in the third sample are 351 skeleton from the Vlach cemeteries dating to the Late Middle Ages and Early Modern Period (14th - 18th century). The results have shown that the populations in all three samples were exposed to roughly the same risk of suffering injuries while performing agricultural works despite the fact that the first and second sample are farming populations, and the third sample consists of transhumant herders. The results have also shown that there was a strict division of labor between males and females, whereby males performed physically harder and more demanding works than the females. In the third sample,males and females worked equally hard, most likely with an aim of adapting to new living conditions as soon as possible.
Keywords: antemortem traumas; long bones; Middle Ages; Vlachs; Croatia; agriculture; transhumant herding